Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1063/1.442080
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectrum, structure, and intramolecular force field of the ArClCN van der Waals complex

Abstract: The rotational spectrum of the ArClCN van der Waals complex has been assigned using pulsed Fourier transform microwave spectroscopy in a Fabry-Perot cavity with a pulsed supersonic nozzle as the molecular source. ArClCN is T-shaped and the data were fit to the Watson rotational parameters and an exact expression for the Cl and N nuclear quadrupole coupling. The spectroscopic constants for Ar35ClCN are A′′ = 6152.5411(21) MHz, B′′ = 1577.0362(8) MHz, C′′ = 1246.7514(6) MHz, τ1 = −576.0(2) kHz, τ2 = −97.28(8) kH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…is the semirigid rotor rotational Hamiltonian, including centrifugal distortion, H quad accounts for nuclear quadrupole coupling, and H Stark = − μ · E (where E is the electric field strength and μ is the molecular electric dipole moment). The Hamiltonian matrix is constructed in the | I , J , F , M F 〉 basis using matrix elements reported previously. The dipole moment of each complex was obtained from a least-squares fit of the observed Stark-shifted frequencies with the rotational and ( 79 Br) nuclear quadrupole coupling constants constrained to their previously determined zero-field values. Examination of the observed Stark shifts indicated that for 15 NH 3 −H 79 Br, the Stark effects were essentially second order, whereas for (CH 3 ) 3 15 N−H 79 Br, H 3 15 N−H 35 Cl and (CH 3 ) 3 15 N−H 35 Cl, significant deviations were observed for some components, requiring the full diagonalization performed by QSTARK .…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…is the semirigid rotor rotational Hamiltonian, including centrifugal distortion, H quad accounts for nuclear quadrupole coupling, and H Stark = − μ · E (where E is the electric field strength and μ is the molecular electric dipole moment). The Hamiltonian matrix is constructed in the | I , J , F , M F 〉 basis using matrix elements reported previously. The dipole moment of each complex was obtained from a least-squares fit of the observed Stark-shifted frequencies with the rotational and ( 79 Br) nuclear quadrupole coupling constants constrained to their previously determined zero-field values. Examination of the observed Stark shifts indicated that for 15 NH 3 −H 79 Br, the Stark effects were essentially second order, whereas for (CH 3 ) 3 15 N−H 79 Br, H 3 15 N−H 35 Cl and (CH 3 ) 3 15 N−H 35 Cl, significant deviations were observed for some components, requiring the full diagonalization performed by QSTARK .…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…[21] Values of D J , B 0 , B H 3 P and B Br 2 are given in Tables 3 and 4, while m has been defined in connection with Equation (6). The resulting values for k s of the six isotopomers of H 3 P´´´Br 2 are identical within experimental error and are listed in Table 5 [a] Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Rotational and centrifugal distortion constants were fitted to the center frequencies rot , using Watson's Sreduction, I r -representation Hamiltonian (28). The resulting spectroscopic constants, including three rotational constants, four quartic centrifugal distortion constants (i.e., D J , D JK , d 1 , and d 2 ), and two sextic distortion constants (i.e., H J and H JK ), as well as the nuclear quadrupole coupling constants aa (1), bb (1), aa (2), and bb (2) are given in Table 2 for both 20 Ne-14 N 14 NO and 22 Ne-14 N 14 NO. The numbers 1 and 2 in the parentheses indicate the terminal and central 14 N nuclei, respectively.…”
Section: A Observed Spectra Assignments and Analysesmentioning
confidence: 99%